Controlling Raw Material Inventory for Methanol Production Using the Silver Meal Method: Pengendalian Persediaan Bahan Baku Penunjang Methanol Menggunakan Metode Silver Meal - Hafidz Raif Harashta; Enny Aryanny (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Effective inventory control is essential for manufacturing firms to ensure operational continuity and cost efficiency. Specific background: Methanol production facilities often experience persistent overstock of supporting chemicals such as Caustic Soda Flake (NaOH) and Sulphuric Acid (H₂SO₄), resulting in increased storage costs and heightened safety risks. Knowledge gap: Prior studies predominantly apply the Silver Meal heuristic to primary raw materials, with limited evidence of its effectiveness for fluctuating supporting materials in high-risk chemical industries. Aims: This study aims to optimize supporting-material inventory using the Silver Meal method to reduce total inventory costs and improve ordering policies. Results: The method produced lower total costs—Rp 4.144.915.411 for Caustic Soda and Rp 1.096.242.822 for Sulphuric Acid—representing reductions of 4.6% and 8.5% compared to the existing approach commonly used in industry. Novelty: The study introduces the application of a heuristic lot-sizing method to hazardous supporting materials using actual operational data, demonstrating its feasibility in chemically sensitive environments. Implications: Findings provide a practical decision-support model for companies to minimize overstock, enhance operational efficiency, and mitigate safety hazards associated with chemical accumulation. Highlights: Highlights the efficiency of the Silver Meal method in reducing total inventory costs. Addresses overstock issues of hazardous supporting materials in methanol production. Provides a practical model for safer and more economical inventory management. Keywords: Inventory Control, Silver Meal, Methanol Production, Supporting Materials, Cost Optimization